SUJET : LA RESISTANCE AU CHANGEMENT CHEZ DES FEMMES VIOLENTES EN COTE D’IVOIRE: CAS DES EXCISEUSES - Opadou Koudou; Traore Fatoumata; Ismaila Bakayoko (European Scientific Journal, ESJ, 2015)
The state of Côte d’Ivoire, has since 1998 undertaken a fight against Female Genital Mutilation (FGM), through actions of prevention, enforcement and management of circumcisers. In 2014, according to UNICEF more than 38% of circumcised women and the practice remains value by more than 14% of the population. This study aims to identify the factors of resistance to change among women circumcisers. The site is Mankono (town in the center west of Côte d'Ivoire), 80 people participated in the survey. Three interacting variables explain resistance to change: The commitment to socio-cultural values linked to the promotion of female circumcision; income or socio-economic gain and low social control. An education policy centered on the girl could mitigate in short-term this phenomenon.